Restructuring Analysis of Troubled Loan Handling Through Rescheduling at KSP Kopdit Obor Mas, Pasar Level Branch - Yasinta Intan Sakera; Wilhelmina Mitan; Yoseph D. Purnama Rangga (LPPM Institut Studi Islam Sunan Doe, 2023)
This study aims to determine the settlement of non-performing loans based on the credit restructuring method through rescheduling. The collection of data used in this paper uses interviews and documentation. This type of data uses a qualitative descriptive analysis. From the results of observations it was concluded that the credit restructuring policy at KSP Kopdit Obor Mas in an effort to save credit through rescheduling had positive results because it did not burden members or cooperatives and had an impact on reducing problem loans / NPL (Non Performing Loans). The SOP for the Credit Collection and Rescue Policy Pattern contains a Default Credit Collection Framework, in which the final settlement of problem loans is based on the decision of the management meeting which can be in the form of Credit Restructuring, Credit Switching, Collateral Sales, or Charge Off.